SHARIA PORTFOLIO BASED ON CONSTANT WEIGHT ALLOCATION ASSET AND DYNAMIC ALLOCATION - Aflaha Vanya Addisty, Shahnaz
In Fiqh literature, saham (stock) are taken from the term musahamah which comes from the word sahm, means part, in this case the share ownership. In the Indonesian capital market, stocks are divided into two types, normal stocks and sharia stocks. Sharia stock are stock that do not conflict with sharia principles. In Indonesia, sharia stocks are regulated by the OJK where the stock that are considered sharia if the stocks included in Daftar Efek Syariah (DES). All of DES stocks are included in the Indonesian Sharia Stock Index, a sharia capital market. In sharia investment, short selling are not allowed. Therefore, this thesis will examine the efficiency of the sharia stock portfolio where the portfolio is divided into two models based on the asset allocation strategy. Constant weight asset allocation and dynamic asset allocation. The portfolio will be evaluate in a period. One year before the pandemic and one year during the pandemic. Before pandemic, portfolio with constant correlation method give better performance than portfolio with single index model. Meanwhile when pandemic, portfolio with single index model give better performance than portfolio with constant correlation methods.